Honour, Violence and Emotions in History - Strange, Carolyn; Cribb, R. B.; Forth, Christopher E. (Bloomsbury Publishing Plc, 2014)
Honour, Violence and Emotions in History is the first book to draw on emerging cross-disciplinary scholarship on the study of emotions to analyse the history of honour and violence across a broad range of cultures and regions. Written by leading cultural and social historians from around the world, the book considers how emotions - particularly shame, anger, disgust, jealousy, despair and fear - have been provoked and expressed through culturally-embedded and historically specific understandings of honour. The collection explores a range of contexts, from 17th-century China to 18th-century South Africa and 20th-century Europe, offering a broad and wide-ranging analysis of the interrelationships between honour, violence and emotions in history. This ground-breaking book will be of interest to all researchers studying the relationship between violence and the emotions.